Multicriteria model for evaluating quality management of professional training - Daiva Andriušaitienė; Vanda Birutė Ginevičienė; Algis Šileika (Business: Theory and Practice, 2008)
What are the possibilities of complex quantitative evaluation of complex social phenomena and professional training in particular? Can these methods be used for multicriteria evaluation of this phenomenon? Are they well-suited for  investigation  and  monitoring  of  professional  training  quality  management?  The  present  paper  aims  at  answering these  questions,  presenting  and  discussing  the  developed  model  of  multicriteria  evaluation  of  professional  training quality  management  and  considering  other  problems  associated  with  multicriteria  evaluation  of  quality  management of professional training. Moreover, presenting the results of pilot quantitative expert evaluation of professional training quality management, the problem of consistency of expert estimates was discussed, the consistency of experts’ estimates of weights and values of the criteria describing quality management of professional training institutions was determined and multicriteria evaluation of the quality of the above schools was made allowing their arrangement in the priority order according to the quality of performance.